Weapons of the Weak: Everyday Forms of Peasant Resistance - Scott, James C. (Yale University Press, 1985)
"Weapons of the Weak" challenges conventional understandings of peasan t resistance by focusing on the subtle, often overlooked ways that pea sants resist domination. Rather than focusing on dramatic uprisings, S cott examines the everyday acts of resistance that occur in the shadow s of power. Key Arguments Resistance is not always visible: Scott argu es that resistance is not limited to organized rebellions. Everyday ac ts like foot-dragging, gossip, feigned ignorance, and petty theft can be powerful forms of resistance. Hidden transcripts: Scott introduces the concept of "hidden transcripts," which are the informal, offstage discourses where subordinate groups express their grievances and resis tance. These transcripts are often hidden from the dominant group. Mor al economy: Scott emphasizes the importance of the "moral economy" of peasant societies, which are based on shared norms of reciprocity and fairness. When these norms are violated, peasants may resist. Hegemony is not complete: Scott challenges the idea that dominant ideologies c ompletely control the minds of subordinate groups. He shows that peasa nts often have their own interpretations of the world and their place in it. The book is divided into three parts: Part I: The Setting: Intr oduces the village of Sedaka in Malaysia, where Scott conducted his re search. It describes the social and economic structure of the village and the changes that were taking place. Part II: The Everyday Forms of Resistance: This section examines the various ways that peasants in S edaka resisted domination. It includes chapters on gossip, foot-draggi ng, sabotage, and other forms of resistance. Part III: The Moral Econo my and the Ideology of Resistance: This section explores the moral eco nomy of the village and how it shapes peasant resistance. It also exam ines the "hidden transcripts" of resistance and the ways that peasants make sense of their world. Key Concepts Weapons of the weak: The ever yday forms of resistance used by subordinate groups. Hidden transcript s: The informal, offstage discourses where subordinate groups express their grievances and resistance. Moral economy: The shared norms of re ciprocity and fairness in peasant societies. Hegemony: The dominance o f a particular set of ideas or beliefs.